Case report: Successful PGT-M based on the identification of a spliceogenic variant in the RPGRIP1L gene through Minigene assay - Xu, Huiling; Pu, Jiajie; Wu, Zhengzhong; Guo, Shuhan; Li, Xuemei (Frontiers in Genetics, 2024)
With the development of high-throughput sequencing, the genetic etiology of many diseases has been revealed. However, this has also led to the categorization of many variants as variants of uncertain significance (VUSs), presenting a major challenge in genetic counseling. A couple with a history of adverse pregnancies sought assisted reproductive technology. Trio-WES revealed that they individually carried the following variants in the RPGRIP1L gene: a c.1581G>A (p.Gln527=) (VUS) and a c.135-11A>G (likely pathogenic variant, LP). Further investigation using the Minigene assay showed that the variant c.1581G>A (p.Gln527=) disrupts the normal splicing pattern of the mRNA, leading to two abnormal splicing modes: 1) retention of 26 bp in intron 13; 2) exon 13 skipping transcript. Consequently, the VUS was reclassified as likely pathogenic. We then performed preimplantation genetic testing (PGT) for the couple, which included direct detection of the RPGRIP1L locus, SNP haplotype analysis, and chromosome copy number detection. Through these precise detection procedures, an unaffected embryo was selected for transfer, and the prenatal genetic diagnosis of the fetus was normal. Our study indicates that the Minigene assay is a valuable tool for splicing functional analysis of variants in vitro. This approach is particularly useful for genetic counseling involving VUS that may affect pre-mRNA splicing, as well as for the subsequent clinical management of the related family.